Cross-aldol reaction of 3-acetyl-2H-chromen-2-one by using Amberlyst 26A as catalyst. Issue 1 (2nd January 2017) - Erşatır, Mehmet; Akbaşlar, Dilek; Demirkol, Onur; Giray, E. Sultan
ABSTRACT: Synthesis of a series of 3-acetylcoumarin-derived chalcones (1a–16a ) was catalyzed with Amberlyst 26A in ethanol. Using reusable Amberlyst 26A and biobased solvent ethanol make this method highly ecofriendly and simple. Amberlyst 26A was found to be a highly effective catalyst for cross aldol reaction. The results shown that the method is operationally simple to implement with a wide scope of substrates. GRAPHICAL ABSTRACT: